Determinants of Stunting in Indonesia: Investigating Key Factors Influencing Child Growth - Lubis, Zulhaida; ., Jumirah; Bukit, Dhani Syahputra (Journal of Ecohumanism, 2024)
Stunting is a condition of growth failure that occurs in children, especially those under the age of five, caused by chronic poor nutritional intake and recurrent infectious diseases. Stunting is a social problem that has an impact on child development and the achievement of human resource quality. This study employed a cross-sectional design to investigate stunting in children in Tapanuli Tengah Regency, North Sumatra, Indonesia. The sample consisted of 402 children from five districts, chosen for their focus on stunting prevention. Data collection involved mother interviews and measuring children’s length/height-for-age indicators. The study examined a variety of family and child characteristics, including age, gender, father’s occupation, family income, birth weight, birth length, and disease history. Multiple Logistic Regression is used to analyze the determinant impact of stunting events on children under five. It was found that 23.4% of stunted children in Tapanuli Tengah Regency. The results of the study show that there was a significant influence of birth length and history of illness on the incidence of stunting. History of illness is the dominant risk factor for stunting, with an odds ratio (OR) of 1.8 with a Confidence Interval (CI) value of 1.120-2. 895. This informs that children who have a history of illness are almost 2 times more likely to be stunted than children who do not have a history of the disease. This study highlights the prevalence of stunting in Tapanuli Tengah Regency and its association with birth length and a history of illness. Interventions to combat stunting should target improving birth length and addressing children’s history of illness. These findings align with existing literature on stunting in Indonesia and underscore the need for targeted interventions. Stunting remains a critical public health concern in Indonesia, necessitating context-specific efforts in Tapanuli Tengah Regency